Antimicrobials and Antimicrobial Resistance (AAMR) - Blower, Isobel (2019)
The antibiotic resistance crisis is threatening the future of modern healthcare and the discovery of solutions will involve collaboration and investigation into multiple avenues of research. This work involved two projects, the first investigating plasmid transmission and the spread of antibiotic resistance genes (ARGs). The second focussed on developing tools to monitor Staphylococcus aureus biofilm growth.